Kebutuhan Dan Ketersediaan Modal Kerja Dalam Hubungannya Dengan Profitabilitas Perusahaan (Studi pada PT. Persada Lampung Raya) - Habiburrahman HABIBURRAHMAN; Daniel Hariadi Sunjoto; Riswan RISWAN (Jurnal Akuntansi dan Keuangan, 2011)
The purpose of this study was to determine how the use of working capital to the company's profitability to fluctuate as well as to determine the exact amount of working capital as needed PT. Lampung Persada Raya. The hypothesis is that "The use of working capital and profitability levels at PT. Persada Raya Lampung Bandar Lampung branch is inefficient".Analysis is performed to determine the optimal amount of working capital is the analysis of sources and uses of working capital, working capital requirements determination analysis, and financial ratios such as liquidity ratios, activity ratios and profitability ratios. The calculations show that the amount of working capital needed by the company is greater than the available working capital. Based on the analysis the authors conclude that the company is likely to experience a shortage of working capital each year. This shows that the company has not been able to optimally manage its working capital in creating maximum profit. Authors suggested the company should be more selective in the use of working capital and more ffective in the management of working capital in order to obtain the optimal profit.